2021
DOI: 10.1093/mnrasl/slab043
|View full text |Cite
|
Sign up to set email alerts
|

Formation of eccentric gas discs from sublimating or partially disrupted asteroids orbiting white dwarfs

Abstract: Of the 21 known gaseous debris discs around white dwarfs, a large fraction of them display observational features that are well described by an eccentric distribution of gas. In the absence of embedded objects or additional forces, these discs should not remain eccentric for long timescales, and should instead circularise due to viscous spreading. The metal pollution and infrared excess we observe from these stars is consistent with the presence of tidally disrupted sub-stellar bodies. We demonstrate, using sm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Five per cent of infrared-bright debris discs around white dwarfs are observed to host an additional gaseous component in emission (Gänsicke et al 2006;Manser et al 2020), identified via the doublepeaked Ca 8600 Å triplet emission profiles produced by a flat, photo-ionised Keplerian disc (Horne & Marsh 1986;Melis et al 2010;Kinnear 2011;Gänsicke et al 2019). The origin of these gaseous components is uncertain, but current mechanisms include: runaway sublimation of dust at the inner edge of the debris disc due to angular momentum conservation (Rafikov 2011;Metzger et al 2012), a collisional cascade of rocky bodies being ground down into dust and gas (Kenyon & Bromley 2017a,b), collisions produced via a tidal stream of planetary debris impacting on a pre-existing disc (Jura 2008;Malamud et al 2021), and a disc-embedded planetesimal that survived the tidal disruption process, inducing the production of gas through collisions or sublimation (Manser et al 2019;Trevascus et al 2021). Recent observations show that variability of the infrared excess from debris discs is common (Xu & Jura 2014;Xu et al 2018;Swan et al 2019;Wang et al 2019), and it has been proposed that the observed variations are due to the production and destruction of dust via planetesimal collisions which could also produce observable gaseous material (Farihi et al 2018;Swan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Five per cent of infrared-bright debris discs around white dwarfs are observed to host an additional gaseous component in emission (Gänsicke et al 2006;Manser et al 2020), identified via the doublepeaked Ca 8600 Å triplet emission profiles produced by a flat, photo-ionised Keplerian disc (Horne & Marsh 1986;Melis et al 2010;Kinnear 2011;Gänsicke et al 2019). The origin of these gaseous components is uncertain, but current mechanisms include: runaway sublimation of dust at the inner edge of the debris disc due to angular momentum conservation (Rafikov 2011;Metzger et al 2012), a collisional cascade of rocky bodies being ground down into dust and gas (Kenyon & Bromley 2017a,b), collisions produced via a tidal stream of planetary debris impacting on a pre-existing disc (Jura 2008;Malamud et al 2021), and a disc-embedded planetesimal that survived the tidal disruption process, inducing the production of gas through collisions or sublimation (Manser et al 2019;Trevascus et al 2021). Recent observations show that variability of the infrared excess from debris discs is common (Xu & Jura 2014;Xu et al 2018;Swan et al 2019;Wang et al 2019), and it has been proposed that the observed variations are due to the production and destruction of dust via planetesimal collisions which could also produce observable gaseous material (Farihi et al 2018;Swan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The sublimated material from an asteroid approaching a white dwarf on an extremely eccentric orbit could quickly accrete onto the white dwarf, or form part of a gaseous debris disc (Trevascus et al 2021). The white dwarf SDSS J1228+1040 is observed with an extremely dense planetesimal orbiting inside a debris disc with a gaseous component expanding out to ∼ 1.2𝑅 (Gänsicke et al 2006;Manser et al 2019).…”
Section: Sublimated Materialsmentioning
confidence: 99%
“…The analytic solutions only result in fallback for e < 1.02. Trevascus et al 2021;Wang et al 2021). We use ∼ 10 6 particles to model the disruption of a solar-like, γ = 5/3 polytrope (with M = M and R * = R ) by a 10 6 M supermassive black hole.…”
Section: Simulation Setupmentioning
confidence: 99%